46. Medical commissioning of a Light Ion Beam Therapy facility: The MedAustron experience of starting up using innovative technology. (December 2017) - Stock, M.; Grevillot, L.; Kragl, G.; Ableitinger, A.; Palmans, H.; Osorio, J.; Böhlen, T.; Gora, J.; Hopfgartner, J.; Letellier, V.; Dreindl, R.; Fuchs, H.; et al.
Abstract : Introduction: One of the methods of acquiring equipment for a Light Ion Beam Therapy (LIBT) facility is to establish collaboration between the customer and one or more manufacturers, so all parties work towards developing the best equipment for the facility. Following this strategy the specifications for a dual particle synchrotron-based facility including accelerator, beam delivery system (BDS), patient alignment systems (PAS), treatment planning systems (TPS), and medical software treatment system have been developed at MedAustron and cooperation activity with the correspondent manufacturers was established. The advantage of having multiple manufacturers was that the MedAustron could select the best equipment available for each component, but on another side the drawback was that in many cases the delivered equipment was at the level of "working prototype" and the acceptance and even commissioning process was used to bring with common effort the prototype to the status of a medical product. This type of implementation requires careful planning and distribution of measurement equipment and human resources. For example, to save time the commissioning of BDS was performed in one treatment room and the commissioning of PAS was simultaneously done in the second room. This allowed effectively using beam time and on later stage to "copy and paste" the calibration results from one room to another. The paper is describing the MedAustron experience in commissioning of a LIBT facility. Methods: The major tasks for commissioning of LIBT facility are to calibrate the various parameters of the BDS and PAS and test these systems under varying clinical conditions, to determine appropriate intervention thresholds, acquire data for entry into the TPS, and perform end-to-end tests for planned patient treatments. Since MedAustron is a dual particle facility, the BDS in two fixed beam rooms is based on the nozzles without movable snouts and hence the same setup is used for carbon ions and protons. In order to preserve ballistic capabilities of protons in a dual-particle facility, the patient needs to be positioned as close as possible to the nozzle and we chose as design a non-isocentric treatment planning and patient positioning system to reduce the air gap. This workflow is supported by a collision avoidance system at different stages of the treatment. It starts with an automated collision detection integrated into the treatment planning phase. In the treatment room robotic table movements, imaging and beam delivery are supported by the record and verify system and checked upfront for collision. Finally, during robot movements the same checks are performed in real time for avoiding potential collision. Results: All involved systems were successfully commissioned and are already in clinical routine operation beginning with the first patient. Using TPS RayStation and specific software there is the possibility at the planning stage to reduce the air gap for each specific proton beam. All parts involved like e.g. the treatment room, patient position system, nozzles, the patient as avatar are modelled and the treatment position is checked for collisions and consequently potential collisions are displayed. In addition the Record and Verify system supports the whole workflow starting from patient step-on, position verification with the ImagingRing™ system and application of the correction vector at the treatment position including the non-isocentric setup. The patient positioning system and the patient position verification system (ImagingRing™) including the tracking camera for correction of the table sag due to the patient weight and application of the correction vector from image registration were also additionally commissioned for that purpose. Conclusions: The MedAustron LIBT facility was successfully commissioned, including setup for non-isocentric proton treatments. In addition the whole workflow was tested via several end-to-end test procedures. With all the effort spend and the highly integrated workflow a high quality of proton treatment within a dual particle facility could be achieved. All patients treated up to now at MedAustron benefited from this possibility.